Skincare Branding Strategies: The Impact of Brand Awareness, Trust, and Image on Purchasing Decisions - Muhammad Rajib Krisnahadi; Dewi Komala Sari; Kumara Adji Kusuma (Jurnal Ilmu Manajemen, 2025)
This study aims to determine the effect of brand awareness, brand trust and brand image on purchasing decisions on skincare skintific Tiktokshop Sidoarjo. This study uses a quantitative approach, for the population in this study is the Sidoarjo community with a sample of 100.The sampling technique uses purposive sampling with the respondent criteria, namely the Sidoarjo community who have purchased skincare skintific tiktok shop. Data collection techniques by distributing questionnaires and answers are measured using a Likert scale. The data analysis technique in this study uses the smart PLS (Partial Least Square) tool. The results of this study prove that Brand Awareness influences purchasing decisions on skincare skintific tiktokshop products. In addition, Brand Trust influences purchasing decisions on skincare skintific tiktok shop products and Brand Image influences purchasing decisions on skincare skintific tiktok shop products